Mekaniska och aktiva egenskaper hos strukturer av nanokristallin cellulosa - Barnå, Gustav; Benjaminsson, John; Clark, Malte; Lundström, William; Preinitz G¨ardinge, Viktor; Young, Alexander (My University, 2023)
Nanotechnology is a field of science involving the manipulation of structures smaller than 100 nanometers, often involving singular molecules or atoms. At this scale, unique material properties that enable new and interesting applications appear. Nanocellulose is a nanomaterial with promising future prospects in this area of research, mainly because of its renewable and biocompatible properties. Furthermore, it is very suitable for chemical modification as the large amount of hydroxyl and sulfate groups easily allow for substitution reactions, in addition to coordination with cations. One purpose of this study was to investigate the possibility of chemically modifying nanocellulose such that it reversibly changes its physical structure when exposed to an external stimuli. More specifically, the possibility of achieving it trough a mechanism known as piezoelectricity, where a material contorts or vibrates as a current or voltage is applied to it, or vice versa, was investigated. Another purpose was to determine the effect of different factors in the manufacturing process on the resulting structure and material properties of nanocellulose-based aerogels. Lastly, gaining insight into how molecular interactions between cellulose crystallites affect observed macroscopic phenomena was a key focus of the study. A major challenge with producing films and aerogels that can bend and compress, respectively, from a renewable and natural source such as cellulose, is its fragility and stiffness. This problem emphasizes the importance of chemical modification and its ability to alter the structure of nanocellulose on a molecular scale, such that it obtains the desired properties. Research on which additives successfully increase the flexibility and piezoelectric properties of nanocellulose is therefore a central part of this review. In order to accomplish this, the task was divided into three main steps. Firstly, manufacturing nanocrystalline cellulose by hydrolysis of microcrystalline cellulose (MCC) with sulfuric acid, followed by producing nanocellulose-based films and aerogels. Secondly, identifying chemical additives or modifications of the cellulose crystallites that provide the durability necessary to repeatedly change the macroscopic structure without fracturing. Additionally, inducing piezoelectric qualities in films by a similar methodology. Thirdly, a quantitative comparison of the mechanical and electrical properties of films and aerogels that passed the initial trials. Consequently, the effects of the chemical modifications and other factors was determined. Triethanolamine proved to be especially successful as a plasticizing additive for the films, providing the greatest increase in flexibility and durability. Moreover, including azetidinium salts in the manufacturing of films resulted in the emergence of stronger piezoeletric effects compared to alternatives, such as triethanolamine and tartaric acid. Aerogels frozen in carbon dioxide ice baths crystallize into a more uniform directional structure, characterized by a distinct horizontal surface layer and vertical fibers throughout, in comparison to their counterparts produced by freezing at -80 °C followed by freeze-drying. Furthermore, this resulted in a more reflective and lustrous surface with better rebound and less structural damage when compressed. In conclusion, modifying nanocellulose films with triethanolamine and azetidinium salts provided the desired mechanical and electrical properties respectively. Moreover, including PVA as an additive followed by freeze drying in carbon dioxide ice baths resulted in more structured, durable and flexible aerogels.